The influence of corneal astigmatism on retinal nerve fiber layer thickness and optic nerve head parameter measurements by spectral-domain optical coherence tomography - Liu Lin; Zou Jun; Huang Hui; Yang Jian-guo; Chen Shao-rong (BMC, 2012)
Abstract Background To evaluate the influence of corneal astigmatism (CA) on retinal nerve fiber layer (RNFL) thickness and optic nerve head(ONH) parameters measured with spectral-domain optical coherence tomography (OCT) in high myopes patients before refractive surgery. Methods Seventy eyes of 35 consecutive refractive surgery candidates were included in this study. The mean age of the subjects was 26.42 ± 6.95 years, the average CA was −1.17 diopters (D; SD 0.64; range −0.2 to-3.3D), All subjects in this study were WTR CA. 34 eyes were in the normal CA group with a mean CA was −0.67 ± 0.28D, 36 eyes were in the high CA group with an average CA of −1.65 ± 0.49D. All subjects underwent ophthalmic examination and imaging with the Cirrus HD OCT. Results No significant difference was noted in the average cup-to-disk ratio, vertical cup-to-disk ratio and cup volume (all P values > 0.05). Compared with the normal CA group, the high CA group had a larger disc area and rim area, thinner RNFL thickness in the temporal quadrant, and the superotemporal and inferotemporal peaks were farther to the temporal horizon (All P values < 0.05). There were no significant differences between the two groups in global average RNFL thickness, as well as superior, nasal and inferior quadrant RNFL thickness (all P values > 0.05). Conclusions The degree of with-the-rule CA should be considered when interpreting ONH parameters and peripapillary RNFL thickness measured by the Cirrus HD OCT. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1148475676881895